Accre 8 emerging point of care CLIA system for vitamin B12 assessment compared with three established assays - Farah M. Trad (22466704) (2025)
Accurate Vitamin B12 (Vit B12) quantification is essential for diagnosing deficiencies linked to neurological and hematological disorders. The Accre 8 Point-of-Care (POC) Chemiluminescent Immunoassay (CLIA) system offers a compact design, rapid single-step operation, and minimal calibration requirements. This study evaluates Accre 8’s performance against established CLIA immunoassays (Abbott and Roche) and LC-MS/MS, the gold standard for Vit B12 quantification. A total of 297 serum samples, spanning deficient to sufficient Vit B12 levels, were analyzed. Accre 8 demonstrated a strong correlation with LC-MS/MS (r = 0.94, p < 0.001), with median Vit B12 levels closely aligning with LC-MS/MS (256.0 pmol/L). Accre 8 exhibited high sensitivity (96.9%) and specificity (86.7%), with Cohen’s Kappa agreement (0.76). Bland-Altman analysis showed a mean bias of - 18.5%, while Passing-Bablok regression indicated proportional bias at higher concentrations (slope = 1.44). ROC analysis confirmed excellent diagnostic accuracy (AUC = 0.98). Accre 8’s strong diagnostic performance, minimal calibration needs, and low sample volume requirements position it as a practical alternative to conventional CLIA systems for Vit B12 assessment, particularly in clinical and resource-limited settings. These findings support its potential integration into routine diagnostic workflows for Vit B12 deficiency screening and monitoring. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-025-97503-4